Phytoplankton Composition of the East Coast of Peninsular Malaysia with Emphasis on Several Potential Harmful Species. - Teng, Sing Tung; Hii, Kieng Soon; Low, Ing Kou; Lau, Winnie L.S.; Amimuliani, Adam; Normawaty, Mohammad Noor; Leaw, Chui Pin; Lim, Po Teen (UMT press, 2019)
A field survey had been conducted during the 15 to 27 August 2016 at East coastline of the Peninsular Malaysia, part of the EPSK Scientific expedition. A total of 59 micro-phytoplankton was collected by using the 20 um plankton net from 10 transect lines along the East coastline of Peninsular. Samples were enumerated to obtain the composition and cell abundance of the micro-phytoplankton. Micro-phytoplankton was identified based on the morphology approach with light microscopy and advanced electron microscopy. A total of 52 genera were documented in this study. Sixteen genera were dinoflagellate and 36 genera were diatom. Chaetoceros was found to be the dominant genus with 49.39% of overall in the East coast of Peninsular. Station 56-59 were showed the highest cell density with 31,691 cells ml-1. Station T5 was showed the lowest cell density with 3,006 cells ml-1. A total of five harmful genera were found in this survey. There were in genera of Alexandrium, Ceratium, Prorocentrum, Pseudo-nitzschia, and Nitzschia.